Translational reprogramming under heat stress: a plant’s perspective - Moray Smith; Aminin Taqrir Akramin; Martin Balcerowicz (Royal Society Open Science)
Plants experience dynamic and sometimes extreme fluctuations in temperature on hourly, daily and seasonal scales, which are becoming increasingly challenging as climate change progresses. To maximize fitness and chances of survival, plants continuously adjust their growth, development and physiology to their temperature environment. Changes in protein synthesis are central to these acclimatization processes, enabling rapid and precise modulation of cellular functions. In this review, we discuss the molecular mechanisms driving heat-induced translational reprogramming, integrating insights from animal and yeast systems with current knowledge and emerging hypotheses in plants. We revisit the core stages of translation—initiation, elongation and termination—and the roles of associated translation factors while also exploring emerging areas of interest, including biomolecular condensates, RNA modifications and cis-regulatory elements. Finally, we consider how a deeper understanding of translational control could be harnessed to enhance crop resilience in the face of climate change.